An Assessment Of New Management Style Of Chinese Family Construction Related Company - Ooi, Hung Nee (2007)
This research is a study of Chinese Family Construction Related Company (CFCRC) that focuses on their philosophy of Chinese management practices and to compare and identify similarities and differences in the management philosophy between the old generation and the new generation style of thinking.Kajian ini mengaji cara-cara pengurusan atas falsafa cina tentang Syarikat Pembinaan Cina dan untuk berbanding and mengenal pasti kesamaan dan perbezaan bagi generasi tua dan generasi baru.